GAMBARAN UMUR WUS MUDA DAN FAKTOR RISIKO KEHAMILAN TERHADAP KOMPLIKASI PERSALINAN ATAU NIFAS DI KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Grace Natasya Putri; Sri Winarni; Yudhy Dharmawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Young fertility woman age is likely to experience problems related to childbirth or postpartum such as pre-eclampsia, eclampsia, hemorrhage, and PROM. In 2010, ASFR 15-19 Central Java is 39 per population. Total deliveries by mother less than 20 years old as many as 125 people in District Bandungan, Semarang regency. The purpose of this study was to analyze the relationship of young fertility woman age and risk factor of pregnancy for labor complications or postpartum childbirth in district Bandungan, Semarang regency. This study was explanatory research using cross sectional design. Data were analyzed by univariate. Sample of this study were 45 women who had given birth at the age less 20 years old of 166 populationusing simple random sampling technique. The results showed the average young fertility woman age is 17,8 years old, hemoglobin concentration with an average 11,2 gr%, size of MUAC with an average 28,5 cm, and the high ANC compliance (86,7%). The average systolic and diastolic blood pressure is 105,2 and 70,9, Most of them were not having complicated childbirth or postpartum (84,4%). Junior and senior high schools institution should cooperate with the local health center to check hemoglobin for early detection from anemia considering the impact of anemia greatly to the health reproduction of woman.